2008
DOI: 10.1016/j.neuropharm.2008.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Calcium release via activation of presynaptic IP3 receptors contributes to kainate-induced IPSC facilitation in rat neocortex

Abstract: We examined the mechanisms of kainate (KA) induced modulation of GABA release in rat prefrontal cortex. Pharmacologically isolated IPSCs were recorded from visually identified layer II/III pyramidal cells using whole cell patch clamp techniques. KA produced an increase in evoked IPSC amplitude at low nanomolar concentrations (100-500 nM). The frequency but not the amplitude of miniature (m) IPSCs was also increased. The GluR5 subunit selective agonist (RS)-2-amino-3-(3-hydroxy-5-tert-butylisoxazol-4-yl) propan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 71 publications
2
24
0
Order By: Relevance
“…A similar mechanism thus appears to be triggered in VP neurons when postsynaptic Ca 2ϩ -permeable Gluk1-containing KARs are activated, leading to the Ca 2ϩ -dependent release of a retrograde signal. Our data, however, do not allow us to assess whether the entry of Ca 2ϩ through GluK1-containing KARs is sufficient by itself to induce the release of dynorphin or whether other mechanisms, such as Ca 2ϩ release from intracellular stores, also contribute to this process (Lauri et al, 2003;Mathew and Hablitz, 2008;Scott et al, 2008).…”
Section: Indirect Inhibitory Action Of Kars On Glutamatergic Inputs Tmentioning
confidence: 75%
See 1 more Smart Citation
“…A similar mechanism thus appears to be triggered in VP neurons when postsynaptic Ca 2ϩ -permeable Gluk1-containing KARs are activated, leading to the Ca 2ϩ -dependent release of a retrograde signal. Our data, however, do not allow us to assess whether the entry of Ca 2ϩ through GluK1-containing KARs is sufficient by itself to induce the release of dynorphin or whether other mechanisms, such as Ca 2ϩ release from intracellular stores, also contribute to this process (Lauri et al, 2003;Mathew and Hablitz, 2008;Scott et al, 2008).…”
Section: Indirect Inhibitory Action Of Kars On Glutamatergic Inputs Tmentioning
confidence: 75%
“…4C,D). We next assessed whether the GluK1 receptors located on VP neurons were permeable to Ca 2ϩ (Lauri et al, 2003;Pinheiro et al, 2007;Mathew and Hablitz., 2008;Sun et al, 2009). In agreement with this hypothesis, we observed that a blocker of Ca 2ϩ -permeable AMPA/KAR, PhTx (3 M) (Fletcher and Lodge, 1996), inhibited glutamate-evoked response obtained in the presence of D-AP-5 (50 M) and NBQX (1 M) to the same extent as UBP302 (43.1 Ϯ 5.4%; n ϭ 7; p Ͻ 0.05), whereas it has no effect in OT neurons (98.1 Ϯ 3.1%; n ϭ 11; p Ͼ 0.05) (Fig.…”
Section: Postsynaptic Kars In Ot and Vp Neuronsmentioning
confidence: 99%
“…Furthermore, Ϸ40% of GAD65/67-positive terminals also expressed the glutamate receptor subunit GluR5, a component of non-NMDA receptors, in mechanically dissociated preparations (4). Indeed, the activation of GABAergic terminals by glutamate could be a widespread mechanism, as a similar facilitatory effect on the release of GABA mediated by kainate receptors has also been described in the prefontal cortex (26,27). We must also consider the possibility that the diffusing glutamate (and other compounds) may reach the inhibitory PSD, and not just the cell membrane of the terminal, evoking the release of GABA.…”
Section: Discussionmentioning
confidence: 95%
“…This finding demonstrates that under certain circumstances, activation of presynaptic GluK1-containing KARs stimulates a metabotropic pathway leading to a decrease in GABA release probability. That facilitation and inhibition of GABA transmission involve an ionotropic and a metabotropic mechanism, respectively, has been already demonstrated in other structures (Rodríguez-Moreno and Lerma, 1998;Jin and Smith, 2007;Mathew and Hablitz, 2008). However, these observations were made separately from each other.…”
Section: Coexistence Of Ionotropic and Metabotropic Kar Modes Of Actionmentioning
confidence: 88%